THE IMPACT OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE AT INDONESIAN FLYING SCHOOL - Widyaningrum , Lia Retno; Amalia, Lia (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Culture has an essential role in an organization, where culture will reflect behavioral processes that have values, beliefs and habits that influence individual attitudes in the organization. This study aims to explore the influence of the role of transformational leadership, organizational culture, and employee engagement on employee performance. The research was conducted in 2022 involving 192 flying school employees in Indonesia. This quantitative research using the Structural Equation Model (SEM) method. The results of the study show that transformational leadership contributes to improving organizational culture and employee performance. Then organizational culture can strengthen employee engagement with the organization and improve employee performance. Employee engagement is also considered capable of improving employee performance. The resulting managerial implications are organizations must be able to choose leaders who are optimistic about the future of the organization, able to provide new insights in completing work, and have self-confidence and capability in their work. Then the organization can apply a culture that is in accordance with organizational goals, and the organization must have a realistic and vision and mission obviously, so that with this clarity employees are able to provide the best performance results for their organization.